A Comparative Study on Different Photovoltaic Array Topologies under Partial Shading Conditions - Jazayeri, Moein; Uysal, Sener; Jazayeri, Kian (IEEE, 2014)
This paper mainly analyzes the performance of different photovoltaic array configurations under various shading patterns. A Matlab/Simulink based simulation model of a PV module is utilized as the smallest building block of the mentioned topologies. The model is validated using the datasheet parameters of the 'SOLAREX MSX-60' PV module. The performance and output characteristics of 'Series-Parallel', 'Total-Cross-Tied' and 'Bridge-Link' array topologies are analyzed and compared using a 6x6 PV array under 6 different shading scenarios. The effects of bypass diodes during partial shading conditions are considered and the analysis results are presented and compared with and without bypass diodes. The mentioned shading scenarios are defined in such a way to simulate the passage of a cloud in different patterns. The results show that all the mentioned topologies have similar performances under identical illuminations while the 'Total-Cross-Tied' (TCT) configuration, despite the high complexity of the system, outperforms both 'Series-Parallel' (SP) and 'Bridge-Link' (BL) structures under partial shading conditions. 'Bridge-Link' and 'Series-Parallel' configurations stand on the 2nd and 3rd performance stages respectively while a Series-Parallel connection presents the least system complexity. The analyses and results provide detailed information on the characteristics of different array topologies which can be utilized by system designers to estimate the power yield and choose the most appropriate system configuration with respect to the existing environmental conditions to improve the overall efficiency.
IEEE PES T and D Conference and Exposition -- APR 14-17, 2014 -- Chicago, IL
Keywords: array configuration; bridge-link; module characteristics; series-parallel simulink; solar cell; solar energy; solar module; total-cross-tied